PENGARUH METODE INTERAKSI PEMBELAJARAN ON CLASS & OFF CLASS TERHADAP MOTIVASI BELAJAR PADA MAHASISWA DI MASA PANDEMI COVID 19 - Kristin E.J Nomleni; Nindya Putri Aprodita (Psikodidaktika, 2022)
Based on the phenomena that are being experienced and propagated in all aspects of life, namely the COVID-19 pandemic, the dynamics related to learning methods become worthy of research, especially in the interaction of lecturers and students that lead to learning motivation. This is because there are so many problems, both personally and technically, that can influence how students learn, especially in a pandemic situation. The purpose of this study was to determine the effect of the learning interaction method on student learning motivation. The approach used in this research is quantitative with a cause-effect approach. The learning interaction method will be measured using 2 variables, namely X1 Interactive Methods & Social Interaction Methods, while the Y variable learning motivation is measured using the EMAPRE-U questionnaire. Questionnaires were distributed to lecturers and students at Bunda Mulia University. The results showed the influence of the two variables on learning motivation, although in practice lecturers mostly used the on-class learning interaction method, it did not rule out the application of the off-class learning interaction method to support students' enthusiasm for learning amid the COVID-19 pandemic situation. In this interaction, students feel cared for and motivated by the lecturers, both in understanding the subject and facing life problems during the COVID-19 pandemic. Keywords: Learning Method, Interaction Method, Learning Motivation, University Student, Lecturer